2020
DOI: 10.1021/acs.jpcb.0c01595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucosylation and O-Acetylation on the Conformation of Shigella flexneri Serogroup 2 O-Antigen Vaccine Targets

Abstract: Shigellosis is an enteric disease with high morbidity and mortality, particularly in developing countries. There is currently no licensed vaccine available. Most infection is caused by Shigella flexneri, of which 30 serotypes have been recognized based on O-antigen polysaccharide structure. Almost all S. flexneri serotypes share the same repeating unit backbone (serotype Y), with varying glucosylation, O-acetylation and phosphorylation. The O-antigen is the primary vaccine target; the vaccine valency (and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…The S. flexneri O-Ags have glycosidic linkages described by two dihedral angles, ϕ and ψ, defined as ϕ = H1-C1-O1-C x ' and ψ = C1-O1-C x '-H x '. These definitions are analogous to ϕ H and ψ H in IUPAC nomenclature and are consistent with our previous carbohydrate modeling [26,38] This work follows our established methodology for the computational study of carbohydrate antigens. Potential of mean force (PMF) calculations for the disaccharide fragments of the O-Ag repeating unit indicate the global minima for each linkage, which are then used to build short 3 RU chains for initial 300 ns MD simulations in solution.…”
Section: Methodssupporting
confidence: 59%
See 4 more Smart Citations
“…The S. flexneri O-Ags have glycosidic linkages described by two dihedral angles, ϕ and ψ, defined as ϕ = H1-C1-O1-C x ' and ψ = C1-O1-C x '-H x '. These definitions are analogous to ϕ H and ψ H in IUPAC nomenclature and are consistent with our previous carbohydrate modeling [26,38] This work follows our established methodology for the computational study of carbohydrate antigens. Potential of mean force (PMF) calculations for the disaccharide fragments of the O-Ag repeating unit indicate the global minima for each linkage, which are then used to build short 3 RU chains for initial 300 ns MD simulations in solution.…”
Section: Methodssupporting
confidence: 59%
“…Figure 3 compares the conformational families for serotype Y (Figure 3a) and the serogroup 2 O-Ags (Figure 3b-d) with the serogroup 3 (Figure 3e,f) and serogroup 5 (Figure 3g,h) O-Ags. As discussed in prior work [26], the flexible Y backbone transitions between extended conformations (Figure 3a Y-1, Y-4, and Y-6) to more curved arrangements of the chain (Figure 3a Y-2, Y-3, and Y-5). Further, we showed that O-factor II (O-4 glucosylation at rhamnose C, serogroup 2) has a dramatic effect on the chain conformations, removing the extended conformations and restricting the O-Ag to a wide range of "C-curves" (Figure 3b).…”
Section: O-ag Flexibilitysupporting
confidence: 57%
See 3 more Smart Citations